Indirect interactions between elephants (Loxodonta africana) and mopane caterpillars (Imbrasia belina) through their shared food resource – mopane trees (Colophospermum mopane) - Du Toit, J.T. (University of Pretoria, 2013)
Thesis (PhD (Zoology))--University of Pretoria, 2007.